AR Mobile Application to Enhance the Birdwatching Experience - Venâncio, José (2021)
Guard@Lis application was developed to ease the birdwatching activity. The main purpose was to support the discovery and identification of bird species along a trail, encouraging the preservation and protection of nature. To create a new bird observation perspective since augmented reality features were developed to enhance the experience of birdwatching, ensuring the chance to watch even the most elusive birds. Adding animated 3D models of some birds allows the observation of these species that, for several reasons, may not be easy to encounter in their natural habitat when the user is making the trail. The solution is composed of a multiplatform app and a back-office. It is prepared to create routes with hotspots and improve the bird species list. This first version was designed with a route in the city of Leiria, having specific points along the way, defined for the observation of certain species. Guard@Lis application intends to encourage the didactic and educational facets, so the whole development process of this application was to create a guide that allows users to be able to identify and list the number of bird species found. At this stage, the app allows its users to trail the main historical and tourist points of Leiria and collect the bird species observed.